Deskripsi Kemampuan Penalaran Matematis Siswa SMK pada Materi Fungsi Komposisi dan Invers - Yosi Adiputra; Handayani Eka Putri (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
ABSTRACT This research aims to provide an overview of the mathematical reasoning abilities of Vocational High School Students on the material of compositional and inverse functions. This research was descriptive qualitative research conducted at SMK Negeri 3 Kuningan in the academic year 2021/2022 in class XI. Samples were taken from as many as 29 students. The data in this research are the results of mathematical reasoning tests. The results of this research show that there are 6.9% of students have reasoning abilities which are included in the very good category, 31.03% of students are included in the good category, 20.7% of students are included in the good category, 31.03% of the students are included in the good category. Less than 10.34% of students fall into the very poor category. The average combined reasoning is 47.84% in the medium category. This research also obtained the most difficult reasoning indicator, namely finding patterns or characteristics of mathematical phenomena for generalization.